Error Analysis in the Formal Training for Simultaneous Interpreting - Oana-Maria Franțescu (Linguaculture, 2020)
Training interpreters is conventionally understood as predominantly ensuring that they have a sufficient amount of practice in specially equipped laboratories and some theoretical knowledge from the field of translation studies. However, despite the established existence of quality standards for interpreters and their work, very little can be standardized in what concerns their training due to the numerous levels of difference between the languages in which interpretars operate. This paper aims to explore the errors occuring in the basic training of third-year students in simultaneous interpreting by using a selected sample of recorded and scripted speeches delivered in class in the original (Source Language) and Target Language versions. The study focuses on the interpreting issues occuring between English and Romanian and explores the factors these issues originate from.